Rancangan Usulan Stasiun Kerja untuk Mengatasi Gejala Musculoskeletal Disorders di PT. X - Joram Wahyu Putra (Jurnal Titra, 2021)
Most of companies have the administration section, at that section most of the works done in front of the computer. Using computer for a long period, lead the body move so limited. Monotous work so easily struck by postural stress that become one of the cause of work related musculoskeletal disorders (WMSDs). PT. X also has the administration section that works in front of the computer for long time period. The research at PT. X in administration section consists of six people that become the research’s object, with the intention to find out the potency WMSDs and give the proposed improvement. Tools or methods that being used are Nordic Body Maps, Rapid Office Strain Assesment (ROSA), and Self Evaluation Checklist for Ergonomic Sitting Posture. Nordic Body Maps that assisted by Mann Whiney as anayltic tool conclude, parts of body that experiencing fatigue significantly are the upper neck, the lower neck, the area of bottom and buttock, and the whole body. The result of ROSA show that 5 of 6 workers need given the corrective action. Some of the proposals’s result to decrease the risk of WMSDs are use of chair that adjustable in height, use of palmrest for keyboard, use of mousepad and the importance of armrest at the seat.The proposal expected can be implemented and can decrease the risk of the workers that sustain WMSDs.